Meet the FRUGALWOODS : Achieving Financial Independence Through Simple Living - Thames, Elizabeth Willard (New York, NY : HarperBusiness, an imprint of HarperCollinsPublishers, 2018)
The personal finance blogger behind Frugalwoods.com relates how she and her husband left their successful careers in the city and embraced frugality to create a more meaningful, purpose-driving life on a homestead in the Vermont woods.
Keywords: Thriftiness; Simplicity; Finance, Personal